Using Linked Data in the Data Integration for Maternal and Infant Death Risk of the SUS in the GISSA Project - Freitas, Renato; Rocha, Cleilton; Braga, Oton; Lopes, Gabriel; Monteiro, Odorico; Oliveira, Mauro (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Making good governance decisions is a constant challenge for Public Health administration. Health managers need to make data analysis in order to identify several health problems. In Brazil, these data are made available by DATASUS. Generally, they are stored in distinct and heterogeneous databases. The Linked Data approach allow a homogenized view of the data as a unique basis. This article proposes a ontology-based model and Linked Data to integrate datasets and calculate the probability of maternal and infant death risk in order to give support in decision-making in the GISSA project.